Biophysical insights to tackle with the coronavirus SARS-COV-2 by UV - Zahra Elyasigorji; Hamid Mobasheri (Wolters Kluwer Medknow Publications, 2020)
World's scientists are taking various approaches to tackle with SARS-COV-2 virus pandemic that was originated from Wuhan, China in late 2019 and caused Covid-19 disease. Researchers found the ultraviolet ability to decontaminate surfaces, air, and water from viruses and bacteria. Different from UVA and UVB, UVC is quite effective in destroying microorganisms. UV from Light Emitting Diodes (LEDs) that are polychromatic rays (10-12nm) are more effective in inactivating microorganisms or viruses than monochromatic (<1nm) ones. The influence of UV on the hydrogen bonds between water molecules affects the protein structure and dynamics of deviating their functions. The degree of bond stretching and vibrations between the hydrogen and oxygen atoms in a water molecule determines its ability to dissociate and act as a catalyst. The UV light adds energy to the water molecules and increases their vibrations to the point where they break up. Following this so-called 'transition state', the water cages in the water networks exposed to hydrophobic and hydrophilic molecules are rearranged and thus, say the rate of ionic flows inside the ionic channel is changed. Accordingly, disturbance in the water network arrangements leads to the disruption of ionic bonds in functional groups of viral proteins and thus, leads to the disruption of the function of ion channels and viral receptors. However, while electromagnetic radiations decrease the virus infectivity, uncontrolled UV irradiation can cause significant harm to human health and other living organisms. Here, the effect of the UV irradiation on the hydration status of virus spike and membrane channel proteins will be discussed. Further, the effects of free radicals formed by irradiated UV on the structure and dynamics of virus exposed proteins will be shown.